2010
DOI: 10.4269/ajtmh.2010.09-0227
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Bats to Leptospirosis Transmission in São Paulo City, Brazil

Abstract: Abstract. The biodiversity of potential leptospiral reservoir hosts is lower in urban than in rural environments. Previous data indicate the potential for bats to act as carriers of Leptospira in regions such as the Amazon of South America and in Australia. Yet, little is known about the contribution of bats to leptospirosis in urban environments in South America. This study aimed to test the hypothesis that bats infected with Leptospira are sources of leptospirosis transmission to humans in São Paulo City, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 16 publications
1
22
1
4
Order By: Relevance
“…carriers. The data showed higher frequency than previous Brazilian studies -39.1% vs 7.8% and 1.75% in Botucatu and São Paulo, respectively [25,26]. This may be related to the environment in which the bats live, as in the present study bats from South Brazilian areas, most of them distant from urban centers, were evaluated.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…carriers. The data showed higher frequency than previous Brazilian studies -39.1% vs 7.8% and 1.75% in Botucatu and São Paulo, respectively [25,26]. This may be related to the environment in which the bats live, as in the present study bats from South Brazilian areas, most of them distant from urban centers, were evaluated.…”
Section: Discussioncontrasting
confidence: 64%
“…In Brazil, more than 60,000 human leptospirosis cases were confirmed between 2000 and 2016 and the regions with higher frequency of confirmed cases are the southern and southeastern regions [3]. The higher incidences occur in low-income populations of most populous cities, such as São Paulo or in regions with poor sanitation system [4]. Besides public health issues, leptospirosis is responsible for economic losses for the animal production sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Matthias et al 22 reported a prevalence of 3.4% in insectivorous bats in the city of Iquitos, a percentage very similar to that described in Brazil 23 , which was 2%. This suggests that bats are not important in the transmission of leptospirosis in this area and possibly in other urban areas with similar characteristics, but could play a role in the maintenance of Leptospira in the environment.…”
Section: Discussionmentioning
confidence: 60%
“…Leptospira interrogans has mainly been identified in domestic mammals because they have direct contact with humans 4 , 5 , 6 . However, in Neotropical areas, such as Panama 21 , the Peruvian Amazon 6 , 8 and the city of São Paulo 16 , some wild mammals (bats, carnivores, marsupials and rodents) have been identified as hosts of L . interrogans .…”
mentioning
confidence: 99%